2017
DOI: 10.1016/j.pharep.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Depressive-like neurochemical and behavioral markers of Parkinson’s disease after 6-OHDA administered unilaterally to the rat medial forebrain bundle

Abstract: Administration of the highest dose of 6-OHDA without desipramine pretreatment evoked neurochemical and behavioral changes resembling the advanced PD with coexisting depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 30 publications
4
26
0
Order By: Relevance
“…We would argue that the former is more likely for the following reasons. First, our previous results confirmed depletion of dopamine on the lesioned side of the frontal cortex of rats that underwent the same treatment (Kamińska et al, 2017). Second, the expression of markers of glial activation (e.g., Gfap and Aif1) appeared normal and not indicative of glial proliferation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We would argue that the former is more likely for the following reasons. First, our previous results confirmed depletion of dopamine on the lesioned side of the frontal cortex of rats that underwent the same treatment (Kamińska et al, 2017). Second, the expression of markers of glial activation (e.g., Gfap and Aif1) appeared normal and not indicative of glial proliferation.…”
Section: Discussionsupporting
confidence: 78%
“…6-OHDA-induced lesioning of dopamine neurons in rats is a widely used model of PD (Simola et al, 2007). Several studies demonstrated differences in IEG induction following administration of a D1like receptor agonist and the contents of dopamine and its metabolites between the lesioned and nonlesioned hemispheres in animals with unilateral 6-OHDA lesions, particularly in the striatum (Berke et al, 1998;Perese et al, 1989;Walker et al, 2013), and in the level of monoamine neurotransmitters in the substantia nigra, hippocampus and frontal cortex (Kamińska et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine depletions (Guiard et al, 2008) as well as chronic administration of 5 mg/kg d-AMP in adolescent rats enhance firing rates of NE neurons in the locus coeruleus, which projects to the prefrontal cortex (Labonte et al, 2012). That alterations in desipramine sensitivity were only noted with minimum response time is consistent with past work on desipramine's motoric effects (Weber et al, 2009) as well as the use of desipramine to treat motor impairment following DA depletions (Kamińska et al, 2017). Our findings show chronic administration of 1 mg/kg d-AMP in adolescence enhances sensitivity to the responseslowing effects of a high dose of desipramine, suggesting NE signaling is altered by lowdose adolescent d-AMP administration.…”
Section: Effects Of Adolescent D-amp On Sensitivity To D-amp Desiprasupporting
confidence: 75%
“…The 16 µg dose of 6-OHDA diminished the sucrose solution preference for 3% both in rats without and with desipramine pretreatment. Besides, 6-OHDA doses also affected the reduction of dopamine contents of brain structures on the ipsilateral side [ 103 ]. Haddadi et al (2015) administered 6-OHDA (8 µg/2 µL) unilaterally into the substantia nigra in male Wistar rats and assessed the catalepsy (bar test) and motor coordination (rotarod test) behavioral tests.…”
Section: Neurotoxins Used To Induce Pd In Vivo Modelsmentioning
confidence: 99%